CAUSATIVE FACTORS OF INCOMPATIBILITY PRODUCTION PROCESS OF ORTHODOX BLACK TEA IN XYZ FACTORY - Yasmin Mutia; Lucyana Trimo (Jurnal Agroindustri, 2019)
PT A is a private companies ranged in the tea processing industry and tea sales in West Java. PT A decreased in domestic tea sales and reverse applies to the demand for tea exports. To overcome this, PT A was expanding its tea commodity business activities by renting a XYZ Factory. However, PT A is faced with a problems where there was no standardization of the orthodox black tea production process consistently at the XYZ Factory. That matter had an impact on the realization of dry tea production and the tea yield that is not accordance with target. So it is necessary to know what incompatibility occurred during the orthodox black tea production process and the factors that caused the incompatibility. This study used a qualitative design with case study research techniques. The data analysis technique used is descriptive with a fish bone diagram as analysis tool. The results showed that a) discrepancy during the black tea production process are there no specifications for the tea top type and the addition of reprocessing material during milling and drying process, b) factors causing discrepancy, namely: not having their own tea estate and black tea whose quality decrease becomes fresh again.PT A merupakan perusahaan swasta yang bergerak di bidang industri pengolahan dan penjualan teh di Jawa Barat. Berdasarkan data penjualan, PT A mengalami penurunan penjualan teh dalam negeri dan berlaku sebaliknya untuk permintaan akan ekspor teh. Guna mengatasinya, PT A melakukan ekspansi dengan memperluas aktivitas usaha komoditi teh. Salah satunya dengan menyewa Pabrik Teh XYZ. Akan tetapi, PT A dihadapkan pada permasalahan dimana belum adanya standarisasi proses produksi teh hitam orthodox secara konsisten di Pabrik XYZ. Hal tersebut berdampak pada realisasi produksi teh kering dan nilai rendemen teh yang tidak sesuai dengan target. Sehingga perlu diketahui ketidaksesuaian apa saja yang terjadi selama proses produksi teh hitam orthodox di Pabrik XYZ dan faktor-faktor penyebab adanya ketidaksesuaian tersebut. Penelitian ini menggunakan desain kualitatif dengan teknik penelitian studi kasus. Teknik analisis data yang digunakan yaitu deskriptif dengan alat analisis diagram tulang ikan. Hasil penelitian menunjukkan bahwa a) ketidaksesuaian selama proses produksi yaitu: tidak ada spesifikasi khusus untuk jenis pucuk yang digunakan dan adanya penambahan bahan reproses saat penggilingan dan pengeringan, b) faktor penyebab ketidaksesuaian yaitu: belum memiliki kebun teh sendiri dan teh hitam yang mutunya menurun agar fresh kembali